Pre-endoscopy serological testing for coeliac disease: evaluation of a clinical decision tool. Issue 7596 (23rd March 2007) - Hopper, Andrew D; Cross, Simon S; Hurlstone, David P; McAlindon, Mark E; Lobo, Alan J; Hadjivassiliou, Marios; Sloan, Marion E; Dixon, Simon; Sanders, David S
Abstract : Objective To determine an effective diagnostic method of detecting all cases of coeliac disease in patients referred for gastroscopy without performing routine duodenal biopsy. Design An initial retrospective cohort of patients attending for gastroscopy was analysed to derive a clinical decision tool that could increase the detection of coeliac disease without performing routine duodenal biopsy. The tool incorporated serology (measuring antibodies to tissue transglutaminase) and stratifying patients according to their referral symptoms (patients were classified as having a "high risk" or "low risk" of coeliac disease). The decision tool was then tested on a second cohort of patients attending for gastroscopy. In the second cohort all patients had a routine duodenal biopsy and serology performed. Setting Teaching hospital in Sheffield. Participants 2000 consecutive adult patients referred for gastroscopy recruited prospectively. Main outcome measure Evaluation of a clinical decision tool using patients' referral symptoms, tissue transglutaminase antibody results, and duodenal biopsy results. Results No cases of coeliac disease were missed by the pre-endoscopy testing algorithm. The prevalence of coeliac disease in patients attending for endoscopy was 3.9% (77/2000, 95% confidence interval 3.1% to 4.8%). The prevalence in the high risk and low risk groups was 9.6% (71/739, 7.7% to 12.0%) and 0.5% (6/1261, 0.2% to 1.0%). The prevalence of coeliac disease in patients who were negative for tissue transglutaminase antibody was 0.4% (7/2000). The sensitivity, specificity, positive predictive value, and negative predictive value for a positive antibody result to diagnose coeliac disease was 90.9%, 90.9%, 28.6%, and 99.6%, respectively. Evaluation of the clinical decision tool gave a sensitivity, specificity, positive predictive value, and negative predictive value of 100%, 60.8%, 9.3%, and 100%, respectively. Conclusions Pre-endoscopy serological testing in combination with biopsy of high risk cases detected all cases of coeliac disease. The use of this decision tool may enable the endoscopist to target patients who need a duodenal biopsy.